Risk factor analysis of plastic bronchitis among 126 children with macrolide-resistant Mycoplasma pneumoniae pneumonia with mutations at the A2063G site after bronchoscopy examination: a nomogram prediction model - Ran Ma; Ting Bai; Bo Yuan; Li Zhang; Shanshan Li; Lanhua Ma; Wei Zhang (Frontiers in Pediatrics)
ObjectiveTo determine the risk factors for plastic bronchitis (PB) in children diagnosed with macrolide-resistant Mycoplasma pneumoniae (MRMP) pneumonia associated with the A2064G variant.MethodsThe clinical data of 126 children diagnosed with MRMP pneumonia (all with mutations at the A2063G site) who underwent bronchoscopy from May 2023 to April 2024 were retrospectively collected. Based on bronchoscopic findings, patients were classified into the PB and non-PB groups. The study compared the general and clinical features, laboratory indicators, imaging features, bronchoscopic manifestations, treatment, and prognosis between the two groups. A nomogram model, based on logistic regression, was developed to estimate the risks of developing PB in children with MRMP pneumonia caused by mutations at the A2063G site.ResultsWe included 68 boys and 58 girls in this study, with 32 (25.4%) belonging to the PB group. The nomogram model constructed in this study indicated that three risk factors—Atelectasis, Mycoplasma pneumoniae genome copies (throat swab) >105, and D-dimer levels—could be used for the early identification of MRMP pneumonia-induced PB. The area under the receiver operating characteristic curve for the predictive model was 0.832 (95% confidence interval: 0.743–0.922). The Hosmer-Lemeshow goodness-of-fit test demonstrated good calibration of the nomogram (P = 0.227, R2 = 0.403). Decision curve analyses revealed that the model has clinical value. Regarding treatment, second-line drugs and the frequency of bronchoscopy were significantly higher in the PB group than in the non-PB group.ConclusionsEarly risk factor identification and bronchoscopy can improve the outcomes of children with PB associated with MRMP pneumonia caused by mutations at the A2063G site.